Regression of liver fibrosis and hepatocellular carcinoma development after HCV eradication with oral antiviral agents - Yoo, Hae Won; Park, Jun Yong; Kim, Sang Gyune; Jung, Young Kul; Lee, Sae Hwan; Kim, Moon Young; Jun, Dae Won; Jang, Jae Young; Lee, Jin Woo; Kwon, Oh Sang (Scientific Reports, 2022)
We prospectively investigated the changes of liver stiffness (LS) and the occurrence of hepatocellular carcinoma (HCC) after hepatitis C virus (HCV) eradication using direct antiviral agents (DAA) over three years. LS measurement using transient elastography and serum fibrosis surrogate markers before treatment and at 48, 96, 144 weeks after starting direct-acting antivirals (DAA) according to the protocol were evaluated. Patients were also compared with historical cohort treated with pegylated interferon (peg-IFN). Sustained viral response (SVR) was observed in 95.8%. LS value in the patients achieving SVR significantly decreased over time (19.4 ± 12.9 kPa [baseline], 13.9 ± 9.1 kPa [48 weeks], 11.7 ± 8.2 kPa [96 weeks], 10.09 ± 6.23 [144 weeks], all p < 0.001). With matched analysis, the decrease in LS value was significantly larger in DAA group than peg-IFN group at both 48 weeks (29% vs. 9%) and 96 weeks (39% vs. 17%). The incidence of HCC was not significantly different between DAA and peg-IFN groups (5.5% vs. 5.4%) at 144 weeks. HCV eradication with DAA can lead to improvement of liver stiffness over time. The regression of fibrosis was greater in the group with DAA than peg-IFN. Clinical trials registration: ClinicalTrials.gov (NCT02865369).